2020
DOI: 10.5114/amsad.2020.103031
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of serum endocan levels in relation to epicardial fat tissue thickness in metabolic syndrome patients

Abstract: IntroductionMetabolic syndrome has been recognized as a predictor of cardiovascular diseases. Epicardial fat tissue (EFT) thickness has recently been shown to be a predictor of cardiovascular diseases in metabolic syndrome patients. Endocan is a novel molecule which is considered to be an early marker of endothelial dysfunction. Our aim was to evaluate endocan serum levels for the first time in metabolic syndrome patients, in relation to EFT thickness.Material and methodsThe study included 44 patients with met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…51 In contrast, an investigation of patients with metabolic syndrome showed a marked decrease in endocan levels in patients compared with controls, with no apparent correlation with epicardial fat tissue thickness. 52 CPAP is an effective treatment to reduce OSA symptoms, improve quality of life, and reduce the risk of long-term complications. Among our included studies, two studies have assessed the association between the endocan plasma levels after receiving CPAP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…51 In contrast, an investigation of patients with metabolic syndrome showed a marked decrease in endocan levels in patients compared with controls, with no apparent correlation with epicardial fat tissue thickness. 52 CPAP is an effective treatment to reduce OSA symptoms, improve quality of life, and reduce the risk of long-term complications. Among our included studies, two studies have assessed the association between the endocan plasma levels after receiving CPAP.…”
Section: Discussionmentioning
confidence: 99%
“…51 In contrast, an investigation of patients with metabolic syndrome showed a marked decrease in endocan levels in patients compared with controls, with no apparent correlation with epicardial fat tissue thickness. 52…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, Arman et al [ 28 ] demonstrated lower levels of circulating endocan in subjects with prediabetes (n = 42) compared to healthy controls (n = 42). Boyuk et al [ 29 ] also recorded lower circulating endocan levels in MetS subjects (n = 44) as compared to MetS-free individuals (n = 26).…”
Section: Endocan and Metabolic Syndromementioning
confidence: 95%
“…Resilience can be understood as a product of the risk that a stressor will occur, the vulnerability to stress, which is the combination of susceptibility and exposure to stress as well as the duration of exposure [16]. For a long time, this concept has been associated primarily with the ability of a system to recover from a disturbance or the changes being implemented [17,18]. Regarding social systems, the process of building resilience emphasizes the importance of unique processes such as adaptation and transformation, which allow societies to respond to various types of threats [19,20].…”
Section: Introductionmentioning
confidence: 99%